A State Law and Education Policy Perspective on National Identity in Border Regions - Syaiful Amin; Tsabit Azinar Ahmad; Basuki Wibowo; Ridwan Arifin; Jefri Rieski Triyanto (Universitas Negeri Semarang, 2026)
This paper examines the role of national education in strengthening Indonesian identity in border regions, where nationalism, state sovereignty, and local identities often intersect. Areas such as Papua, North Kalimantan, and Aceh face distinct challenges due to historical tensions, geographic isolation, and political dynamics. The study analyzes how the national education system can promote a cohesive Indonesian identity while accommodating diverse local contexts. Using a qualitative legal and policy approach, the paper reviews key regulations, including the National Education System Law (No. 20/2003), to assess their effectiveness in fostering national unity. The findings indicate that although existing policies emphasize nationalism, they frequently overlook the specific needs and historical experiences of border communities, contributing to identity tensions. This research highlights gaps in the current legal framework and proposes integrating region-specific content into the national curriculum to create a more inclusive approach to identity-building. It argues that a balanced model—combining national values with local relevance—can strengthen both unity and legitimacy in border areas. The paper concludes by recommending legal reforms to enhance regional flexibility in educational content while maintaining national principles of sovereignty and cohesion. Suggested measures include revising the National Education System Law and expanding the Local Government Law (No. 23/2014) to support context-sensitive curriculum development aligned with both local histories and national identity.